Ternary pentagonal BNSi monolayer: Two-dimensional structure with potentially high carrier mobility and strong excitonic effects for photocatalytic applications - Varjovi, M. Jahangirzadeh; Kilic, M. E.; Durgun, E. (AMER PHYSICAL SOC, 2022)
In recent years many attempts have been made to discover new types of two-dimensional (2D) nanostructures with novel properties beyond the hexagonal crystals. The prediction of pentagraphene has sparked a great deal of research interest to investigate 2D pentagonal systems. In line with these efforts, in this paper, we propose a 2D ternary pentagonal monolayer of BNSi (penta-BNSi) and systematically investigate its structural, vibrational, mechanical, piezoelectric, electronic, photocatalytic, and optical properties by performing first-principles methods. We verify the stability of the penta-BNSi monolayer from the dynamical, thermal, and mechanical aspects based on phonon dispersion, ab initio molecular dynamics, and elastic tensor analysis, respectively. The mechanical properties are examined by calculating in-plane stiffness (Y-2D), Poisson's ratio (v), and ultimate tensile strength and penta-BNSi is found to be soft and ductile. The electronic structure and electronic transport calculations indicate that the penta-BNSi monolayer possesses a quasidirect band gap and anisotropic, potentially high carrier mobility. Due to the noncentral symmetric character and semiconducting feature, an intrinsic piezoelectric response emerges in the structure. In addition, penta-BNSi has a suitable band gap as well as proper band edge positions for photocatalytic water splitting within practical pH levels. The analysis of optical properties, including many-body effects, points out strong exciton binding and high light absorption in the visible and near-UV parts of the spectrum. Our findings not only expand the family of 2D pentagonal materials but also uncover an ideal ultrathin material for photocatalytic applications.